Unresolved irony and the late novels of Henry James - Heyns, Michiel W. (Stellenbosch : Stellenbosch University, 2012)
ENGLISH ABSTRACT: This thesis examines the late novels of Henry James in the light of a distinction between "resolved" and "unresolved" ironies. The first chapter aims to clarify this distinction, arguing that in "traditional" ii'onie works the dominant irony is characteristically "resolved": that is, such works are structured upon the gradual enlightenment of the protagonist, to issue in the extinction of irony as such a protagonist achieves equality of insight with the reader. Such resolution, it is argued, is dependent on the author's access to and acceptance of a stable system of values. Conversely, where such stable communal values seem to the writer to be inconsistent with the unstable reality he perceives, the dominant irony of the work, in not being based upon a clearly defined or implied norm, is likely to remain "unresolved". The second chapter approaches the nineteenth-century novel as the product of a society generally perceived to be based on firmly established values. Resolved irony thus predominates in these novels, but not as the vehicle of a complacent view of society: the irony is usually dependent on the perceived need for change in society, its resolution being posited on a belief in the possibility of such change. As such a belief weakens, an unresolved element becomes more evident in these novels, to predominate by the end of the century. The third chapter uses James' The Ambassadors to show how unresolved irony can result from an author's exploration of his subject beyond the confines of his declared intention. In thi's instance, it is argued, the unresolved irony is a function of a more complex view of his pro, tagonist than James seems to have foreseen. The fourth chapter develops this enquiry by showing that in The Wings of the Dove James' subject once again grew beyond the projected outline, but in this case with James fully avlare of the development. Unresolved irony, though still a product of "unintended" meanings, thus more consciously reflects a critical view of its subject. The fifth chapter adduces The Goleen Bowl as James' most sustained work of unresolved irony. It is the aim to demonstrate that the novel's meaning is entirely a function of this lack of resolution, the controlling vision being that of a society in which professed values are hopelessly at odds with true motives. Joseph Conrad and D.H. Lawrence are consistently used for comparison and contrast with James, partly to demonstrate their awareness of the attractions· and dangers of irony as a response to perplexity, and partly to claim for James a place next to them as a profound commentator on the early twentieth century.